Death by prescription the shocking truth behind an overmedicated nation - Strand, Ray D.; Wallace, Donna K (Thomas Nelson, 2003)
Experienced family doctor Ray Strand writes his patients prescriptions every week, but he also believes that prescribing drugs should be a last resort in most medical cases-not a first choice. In Death by Prescription he provides simple guidelines to help readers protect themselves and their families from suffering adverse reactions to prescription medication